The association between maternal pre‐pregnancy BMI, gestational weight gain and child adiposity: A racial‐ethnically diverse cohort of children. Issue 8 (15th March 2022) - Hunt, Kelly J.; Ferguson, Pamela L.; Neelon, Brian; Commodore, Sarah; Bloom, Michael S.; Sciscione, Anthony C.; Grobman, William A.; Kominiarek, Michelle A.; Newman, Roger B.; Tita, Alan T.; Nageotte, Michael P.; Palomares, Kristy; et al.
Summary: Background: The prevalence of obesity in US children has more than tripled in the past 40 years; hence, it is critical to identify potentially modifiable factors that may mitigate the risk. Objectives: To examine the association between maternal pre‐pregnancy body mass index (BMI), gestational weight gain (GWG) and child adiposity as measured by BMI, waist circumference and percent body fat in a racial‐ethnically diverse cohort. Methods: In a prospective cohort study of healthy women without chronic disease, we examined the association between pre‐pregnancy BMI, GWG and child adiposity. Children ages 4–8 years ( n  = 816) in the Environmental Influences on Child Health Outcomes‐NICHD Fetal Growth Studies were assessed. Trained study staff ascertained maternal pre‐pregnancy BMI, GWG and child adiposity. Results: The odds of child obesity (≥95th BMI percentile) increased independently for each unit increase in maternal pre‐pregnancy BMI [OR = 1.12 (95% CI: 1.08, 1.17)] and for each 5‐kg increase in GWG [OR = 1.25 (95% CI: 1.07, 1.47)]. The odds of child waist circumference (≥85th percentile) also increased independently for pre‐pregnancy BMI [OR = 1.09 (95% CI: 1.05, 1.12)] and GWG [OR = 1.18 (95% CI: 1.04, 1.34)]. Conclusions: Maternal pre‐pregnancy BMI and GWG were each independently and positively associated with child obesity and high child waist circumference.